Statistics. Basic principles - Shyriaieva, N. V. (NTU "KhPI", 2015)
The text contains lecture notes of the general theory of statistics, including clustering statistics, absolute, relative and average values, organization and grouping of data, sampling, correlation and regression analysis, estimation, time series, indexes and their use in economics. Typical examples of solving the material are= presented in the text. Designed for students of bachelor level in 6.030601 "Management" and 6.030508 "Finance and Credit".

Текст лекцій містить основи загальної теорії статистики, включаючи групування статистичних даних, абсолютні, відносні і середні величини, статистичні розподіли, вибіркове спостереження, кореляційно регрессійний аналіз, оцінювання, ряди динаміки, індекси та їх використання в економіко-статистичних дослідженнях. Представлено типові приклади з розв’язаннями за матеріалом, що вивчається. Призначено для студентів напрямів 6.030601 «Менеджмент» та 6.030508 «Фінанси і кредит».
Статистика. Основні принципи
Keywords: statistics; time series; measures of central tendency; sipmle regression